Fear of Falling, Lower Extremity Strength, and Physical and Balance Performance in Older Adults with Diabetes Mellitus. (5th June 2020) - Vongsirinavarat, Mantana; Mathiyakom, Witaya; Kraiwong, Ratchanok; Hiengkaew, Vimonwan
Abstract : Fear of falling (FoF) is known to affect the physical activities and quality of life of older adults with type 2 diabetes mellitus (DM). Many complications of DM, especially ones distressing lower extremity (LE), could lead to increased fall risk and FoF. This study aimed to explore the relationship between FoF, LE muscle strength, and physical performance in older adults without diabetes mellitus (ONDM) and with DM (ODM) with varying degrees of balance impairment. The participants comprised 20 ONDM and 110 ODM. The ODM was grouped by the number of failed performances of the modified clinical test of sensory interaction and balance (mCTSIB). The scores of FoF, balance performance of mCTSIB, physical performance of TUG, and LE muscle strength were compared between groups. The results showed that FoF was present in 30% and 60% of the ONDM and ODM, respectively. Forty percent of the ODM failed one condition of the mCTSIB, while 18% and 16% failed two and three conditions, respectively. As the number of failed performances on the mCTSIB increased, the proportions of participants with FoF significantly increased. The psychosocial domain of FoF, LE muscle strength, and TUG score was significantly different between groups and more affected in the ODM with a greater number of failed performances on the mCTSIB. In conclusion, the mCTSIB can differentiate the varying degrees of balance impairment among ODM. FoF, LE muscle strength, and physical performance are more affected as the degree of balance impairment increases. Comprehensive management related to balance and falls in the ODM should include a regular evaluation and monitoring of standing balance, LE muscle strength, physical performance, and FoF.